Circular Entrepreneurship in Emerging Markets through the Lens of Sustainability - Dantas, Rui Miguel (2022)
The purpose of this research paper is to explore the antecedents and consequences of circular entrepreneurship in emerging markets. The consequences of circular entrepreneurship will be explored through the lens of three dimensions of sustainability: social, economic, and environmental. This study used a multi-case approach, which is frequently applied in circular business literature. The study used convenient and purposeful sampling techniques to identify circular entrepreneurs starting a business by recognizing opportunities in CE. We interviewed the 15 entrepreneurs (all participants engage in plastic circular entrepreneurship) with more than 8 years of experience. We employed a semi-structured interview method because respondents explored important information during the interview. Atlas.ti, a prominent qualitative software package, was used for analysis. This study portrays the antecedents and consequences of circular entrepreneurship identified when circular entrepreneurs take the initiative to serve low-income customers. This study points out that circular entrepreneurs can be motivated both intrinsically and extrinsically. The consequences of circular entrepreneurship show how such enterprises impact on society, sustainability, and the economy. The study points out that circular entrepreneurship can have both positive and negative impacts on the environment. By investigating the determinants and consequences of circular entrepreneurship in emerging markets, the authors make a significant contribution to the field of circular economy and entrepreneurship. We have limited logistics and resources, thus we did not collect data from stakeholders, who might provide a richer picture and insights into how circular products affect their lifestyle. Policymakers can get a better understanding of such enterprises from the findings of this study. They should reassess policies regarding circular entrepreneurship and suggest ways to promote open innovation within circular entrepreneurship. Circular enterprises serve low-income customers by offering an affordable product with attractive features. The government should develop an open innovation action-packed forum to find, design, and create prototypes, as well as introduce more comprehensive sustainable solutions for wastable plastic products.